A Collaborative Study Promoting the Integration of Oral Communication in Virtual Pre-Service Teacher Education - Cormier, Gail; Morneau, Marie-Josée (Journal of the Canadian Association for Curriculum Studies, 2023)
The health protocols generated by the COVID-19 pandemic have limited opportunities for exchange and discussion in the classroom (Carpentier & Sauvageau, 2021) and among colleagues. Yet oral communication is an essential component in the learning process (Hattie, 2017). In the spring of 2021, as professors in the Faculty of Education at the Université de Saint-Boniface, we began a collaborative autoethnographic research project (Taylor & Coia, 2020) to showcase our professional evolution in the context of teaching in virtual mode. Our specific aim was to analyze our pedagogical choices in fostering oral skills in our students. Our vignettes thus focus on our objectives and questions regarding the use of oral expression in initial training activities, our successive pedagogical adaptations and our avenues for improvement. We believe that an emphasis on the oral in teacher education offers opportunities for the co-construction of knowledge, language, cognitive and pedagogical development, as well as contributing to the linguistic vitality of a minority group (Plessis-Bélair et al., 2017; Swain & Watanabe, 2013). We sought to improve our pedagogical practices, and thus better train future teachers, by influencing their role in the teaching of oral language, regardless of their future teaching contexts.